2005
DOI: 10.1109/tns.2005.855817
|View full text |Cite
|
Sign up to set email alerts
|

Neutron effects on short circuit currents of op amps and consequences

Abstract: Discrete bipolar operational amplifiers were irradiated with neutrons in order to study the evolution of the short circuit currents. Also, this paper explores the effect of the reduction of this current in devices based on operational amplifiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Indeed, there is a specific parameter, the PSRR [14], that links V OS and ±V CC and a great deal of data about this parameter can be found on public databases [26]. However, the experimental results reported in this paper along with some others found in the literature [27] demonstrate that a lot of the main op amps characteristics may be dependent on the power supply values after suffering radiation damage and not only the PSRR value, as it is usually believed. …”
Section: A Increasing Influence Of Power Supply Valuesmentioning
confidence: 93%
“…Indeed, there is a specific parameter, the PSRR [14], that links V OS and ±V CC and a great deal of data about this parameter can be found on public databases [26]. However, the experimental results reported in this paper along with some others found in the literature [27] demonstrate that a lot of the main op amps characteristics may be dependent on the power supply values after suffering radiation damage and not only the PSRR value, as it is usually believed. …”
Section: A Increasing Influence Of Power Supply Valuesmentioning
confidence: 93%
“…Previous works [7], [22] have demonstrated that the op amps short circuit current is very affected by the radiation damage and may fall from values on the order of 20-40 mA down to a value lower than 1 mA. In this situation, it will not be strange that the highest current that the op amp may deal with is lower than I 1 .…”
Section: Collapse Of the Primary Op Amp In Pa1xmentioning
confidence: 94%
“…typical class AB stage found in low signal devices [22]. In fact, the output structure is class A in OPA541 and C in PA61, the PA1X devices being class AB amplifiers (Figs.…”
Section: Test Set-upmentioning
confidence: 98%
“…The reason of this drop must be sought in the degradation of the operational amplifier attached to the voltage reference, theory that has been fully developed in [12].…”
Section: 1) Ad565ajdmentioning
confidence: 99%